Streaming Science #1: An Introduction to Using Mobile Technologies for Engagement with Your Target Audience - Peyton Beattie; Jamie Loizzo (EDIS)
This first publication in the Streaming Science EDIS series is focused on how to use mobile hardware and software for engagement with your target audience. This article and series emphasize the creation of communication and educational content via mobile technologies, can be useful for communicators and educators in a variety of settings, and can guide the development of digital engagement experiences for youth and adult audiences. Written by Peyton Beattie and Jamie Loizzo; 3 pp. https://edis.ifas.ufl.edu/wc397